Efficacy of Fungicides against Sclerotium rolfsii Causing Collar Rot of Lentil (Lens culinaris Medik) in West Bengal - Mondal, Amitava; Sadhu, Supratim; Bandyopadhyay, Sayani; Saha, Pratik; Kalindi, Dharmadas; Das, Srikanta (International Journal of Economic Plants, 2026)
The experiment was conducted during rabi (November, 2018 to March, 2019) at the Plant Pathology Laboratory, Faculty of Agriculture, Bidhan Chandra Krishi Viswavidyalaya, Mohanpur, Nadia, West Bengal, India to study the efficacy of fungicides against collar rot pathogen Sclerotium rolfsii isolate SRC1 under laboratory condition. The collar rot disease of lentil was found to be severe, with disease incidence and associated losses reaching up to about 60% in some parts of North India, where the crop was grown after rice, resulting into wilting of the seedling in the early stages of plant growth.. In this study we have used five fungicides to check their efficacy for inhibiting the growth of mycelia and to reduce the sclerotia formation by the isolate SRC 2 at different concentrations viz., 10, 25, 50, and 100 ppm. Fungicide efficacy was quantified by radial mycelial growth (mm) and percent inhibition at 2–4 DAI. Azoxystrobin 18.2% + Difenoconazole 11.4% SC showed the highest suppression of Sclerotium rolfsii, achieving 86.7–99.2% growth inhibition and reducing radial growth to ≤0.38 mm at 100 ppm. Mancozeb 75% WP recorded 79-83% inhibition, whereas other fungicides showed comparatively lower effects, confirming a clear dose-dependent inhibition of the pathogen.